Analysis the Internalization of Core Values at UNIDA Gontor Business Unit - Anggara, Fajar Surya Ari; Widodo, Wahyu (Journal of Management and Business Review, 2022)
This research aims to obtain the results of an analysis of how to internalize basic values in the business unit of the University of Darussalam Gontor in human resource development. This research was conducted using field research. The research was conducted by the Business Unit of The University of Darussalam Gontor, located on the Siman Highway, Siman Subdistrict, Ponorogo Regency, East Java Province. Informants in this study include 1 President Director, 2 Company Managers, 2 Staff who are also Students, and 1 Permanent Employee in the Business Unit of The University of Darussalam Gontor. In this study, the type of observation used passive participation means that researchers are not involved in the Business Unit activities of The University of Darussalam Gontor. Researchers conduct interviews with a free but controlled system, where the interview does freely what the interview will do to the interviewer but still leads to talks. The results showed that the implementation of internalization of basic values including Sincerity, Simplicity, Independence, Ukhuwah Islamiyah or Togetherness, and Freedom in the development of human resources Business Unit Darussalam Gontor University has been in accordance with the theory of internalization stages, internalization strategy, training and development methods and has a function to improve the moral and moral human resources. Further quantitative analysis is needed, such as analyzing influential variables to enhance the performance of the Business Unit of Universitas Darussalam Gontor.